Bismuth-Based Triple Therapy with Bismuth Subcitrate, Metronidazole and Tetracycline in the Eradication of Helicobacter pylori: A Randomised, Placebo Controlled, Double-Blind Study - Sander Veldhuyzen van Zanten; Alain Farley; Norman Marcon; Raymond Lahaie; André Archambault; Richard Hunt; Robert Bailey; David Owen; Jean Spénard; Alan Stiglick; Nick Aimola; Patrick Colin (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine the rate of Helicobacter pylori eradication following bismuth-based triple therapy with colloidal bismuth subcitrate, tetracycline hydrochloride and metronidazole.